Molecular Mechanisms for Regulating Postnatal Ductus Arteriosus Closure - Hung, Yu-Chi (Int J Mol Sci, 2018)
The ductus arteriosus (DA) connects the main pulmonary artery and the aorta in fetal circulation and closes spontaneously within days after birth in normal infants. Abnormal patent DA (PDA) causes morbidities and mortality, especially in preterm infants. Closure of the DA is a complex interactive process involving two events: functional and anatomic closure. Functional closure by smooth muscle contraction was achieved through the regulatory factors of vaso-reactivity. These factors include oxygen sensing system, glutamate, osmolality, prostaglandin E(2), nitric oxide, and carbon monoxide. Anatomic closure by vascular remodeling involved several vascular components including endothelium, extracellular matrix, smooth muscle cells, and intraluminal blood cells. Despite advances in understanding of PDA pathogenesis, the molecular mechanism for regulation of DA closure is complex and not fully understood. In this article we review recent evidence regarding the molecular mechanisms of DA closure.